Pengembangan Usaha Produk Perikanan Yang Bernilai Tambah Dari Hasil Samping Tulang Ikan Dan Daging Bagi Masyarakat Sekitar Pondok Pesantren Almurrabby Kabupaten Kubu Raya - Evi Fitriyani; Ika Meidy Deviarni; Nani Nur’aenah; Dr Teguh Setyo Nugroho (Politeknik Negeri Pontianak, 2021)
The training for the application of science and technology was carried out in the community around the Al Murrabby Islamic Boarding School, Sungai Rengas Village, Kubu Raya Regency with the aim of providing insight into the processing of fishery products. This can be seen from the condition of the fish cultivated by ponds in the village of Sungai Rengas. It is seen that they are sometimes underutilized optimally and are not handled and just left alone. Through the community-based science and technology transfer program (PPM), it is hoped that the community's understanding of the development of fishery products can increase, besides that the potential of marine catch and aquaculture fisheries are optimally utilized and community income will increase. PPM activities carried out include 1) counseling / lecturing activities, 2) Product processing practices / training / demonstrations, 3) Activity modules and guidelines, and 4) Monitoring and evaluation of the results of training activities. The results of this activity can be seen from the results of the questionnaire which shows that after receiving the training the participants are very enthusiastic and have the desire to open their own business in the hope of increasing their income and welfare. It is hoped that this activity will be sustainable, such as the development of processed other fishery products, community assistance both in technology transfer and development of production facilities as well as easy access to capital assistance. Keywords : processing of by-products, training / counseling, increasing income